Comparative evaluation of adverse drug reactions in patients of acne prescribed with either topical benzyl peroxide or retinoic acid in a tertiary care teaching hospital - Pandya, Ishan; Pandya, Purna; Pethani, Neha; Shah, Rima Bharatbhai (International Journal of Research in Dermatology, 2017)
Background: To evaluate and compare the profile of adverse drug reaction, its causality, severity and preventability in patients of acne prescribed with either topical benzyl peroxide or topical retinoic acid in a tertiary care teaching hospital. Methods: Two hundred patients attending to dermatology department with acne and prescribed with either topical benzyl peroxide or topical retinoic acid were observed for occurrence of adverse drug events (ADEs). ADEs were either spontaneously reported or elucidated from personal interviews and analyzed. Results: Out of total 200 patients, 110 (55%) were given benzoyl peroxide gel (2.5%) and remaining 90 (45%) were given retinoic acid cream (0.025%). Total 54 adverse events were reported in 47 (23.5%) patients. Highest number of patients having ADR was from 16-20 years (35, 74.46%) with male predominance (59.57%). Number of adverse events reported was significantly higher (p <0.05) in retinoic acid group (34, 62.96%) as compare to benzyl peroxide group (20, 37.03%). Most common ADRs were exfoliation (14, 25.92%) and burning sensation (13, 24.07%). Most of the ADRs fell in category of ‘probable’ and ‘possible’ in causality assessment by both WHO-UMC method and Narenjo’s scale. All the ADRs were of mild (44, 81.48%) and moderate (10, 18.52%) severity. Majority of ADRs were not preventable (24, 44.44%) followed by definitely preventable 22(40.74%) and 8 (14.81%) probably preventable. Conclusions: ADRs is a common problem associated with topically used medications for acne and its occurrence is significantly higher with retinoic acid as compare to benzyl peroxide. Early diagnosis and proper education about use of topical drugs can prevent some of the ADRs.